Cigarette Use and Adolescent Metabolic and Bariatric Surgery. Issue 3 (2nd February 2021) - Zeller, Meg H.; Kidwell, Katherine M.; Reiter‐Purtill, Jennifer; Jenkins, Todd M.; Michalsky, Marc P.; Mitchell, James E.; Courcoulas, Anita P.; Inge, Thomas H.
Abstract : Objective: This study aimed to track conventional cigarette smoking behaviors and associated correlates in adolescents with severe obesity who did or did not undergo metabolic and bariatric surgery to 4 years after surgery/baseline. Methods: Utilizing a prospective controlled design, surgical ( n  = 153; mean BMI = 52) and nonsurgical ( n  = 70; mean BMI = 47) groups that completed assessments before surgery/at baseline and at Years 2 and 4 post surgery (Year 4: n  = 117 surgical [mean BMI = 38]; n  = 56 nonsurgical [mean BMI = 48]) were compared. Separate logistic regression models tested correlates of Year 4 current smoking. Results: More than half of participants (surgical: 55%; nonsurgical: 60%) had ever smoked a cigarette, with current smoking increasing with time. Groups did not differ in Year 4 current smoking (surgical: 23%; nonsurgical: 33%), with ≈ 50% meeting criteria for "heavy" smoking (≥ half pack/day) and ≈ 40% smoking their first cigarette before ninth grade. Factors associated with higher odds of Year 4 current smoking included dysregulation ( P  < 0.001), internalizing symptoms ( P  = 0.01), alcohol use ( P  = 0.04), caregiver smoking ( P  < 0.001), friend smoking ( P  = 0.001), and perceiving low harm ( P  = 0.02), plus greater percent weight loss ( P  = 0.03) in the surgical group. Conclusions: Smoking is a clinical health challenge for adolescents and young adults with severe obesity, including those who have undergone metabolic and bariatric surgery. Upstream identification, monitoring, and intervention to prevent smoking uptake and escalation in youth with obesity across settings should be prioritized.